Molecular determinants and genetic modifiers of aggregation and toxicity for the ALS disease protein FUS/TLS. - Zhihui Sun (Public Library of Science (PLoS), 2011)
TDP-43 and FUS are RNA-binding proteins that form cytoplasmic inclusions in some forms of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD). Moreover, mutations in TDP-43 and FUS are linked to ALS and FTLD. However, it is unknown whether TDP-43 and FUS aggregate and cause toxicity by similar mechanisms. Here, we exploit a yeast model and purified FUS to elucidate mechanisms of FUS aggregation and toxicity. Like TDP-43, FUS must aggregate in the cytoplasm and bind RNA to confer toxicity in yeast. These cytoplasmic FUS aggregates partition to stress granule compartments just as they do in ALS patients. Importantly, in isolation, FUS spontaneously forms pore-like oligomers and filamentous structures reminiscent of FUS inclusions in ALS patients. FUS aggregation and toxicity requires a prion-like domain, but unlike TDP-43, additional determinants within a RGG domain are critical for FUS aggregation and toxicity. In further distinction to TDP-43, ALS-linked FUS mutations do not promote aggregation. Finally, genome-wide screens uncovered stress granule assembly and RNA metabolism genes that modify FUS toxicity but not TDP-43 toxicity. Our findings suggest that TDP-43 and FUS, though similar RNA-binding proteins, aggregate and confer disease phenotypes via distinct mechanisms. These differences will likely have important therapeutic implications.